Women and work in Russia, 1880-1930 : a study in continuity through change / Jane McDermid and Anna Hillyar. - McDermid, Jane (Longman, 1998)
This study considers the impact of the upheavals in Russian women's working lives caused by industrialization, revolution and World War One. It looks at women from all social classes and makes use of original source material to explore specific lives.
Keywords: Women -- Employment -- Russia -- History -- 19th century; Women -- Employment -- Soviet Union -- History; Women employees -- Russia -- Social conditions; Women employees -- Soviet Union -- Social conditions